交错轴斜齿轮的设计及参数化建模分析 - 王刚 (Jixie chuandong)
Through theoretical calculation and analysis,the crossed axis helical gear is designed with any shaft angle and center distance.The spiral line and the end surface involute tooth profile are created based on Pro/E software.By using the programmodules,the crossed axis helical gearmodel is built.The crossed axis helical gearof any conditionswill be quickly generated when the basic parameters is changed.Then,the modal value and bending strength is obtained by the finite element analysis of the gear.